Types of further qualification of the kindergarten teachers - Mironiuk-Netreba, Alicja (Nauczyciel wczesnej edukacji wobec zmian społeczno-kulturowych, 2016)
Teacher’s professionalism depends on lifelong education. This professional development may take different forms. According to the educational law, a professional teacher undergoes certain stages of promotion. Institutional forms of futher education, with certificates and official notes are an example of formal education. Cooperation of teachers (between counsellor and intern), especially in self-teaching school groups are forms of nonformal education. Another form is informal education which pentains to lifelong self-learning in everyday life and critical or creative analysis of a social reality.